Vers une démocratisation de l’éducation et de la formation par les MOOC ? Étude des caractéristiques des utilisateurs de la plateforme France Université Numérique - Éléonore Vrillon (Recherches en Éducation)
Massive Open Online Courses (MOOC) growth has been rich and worldwide in a few years. A real enthusiasm characterized that development perceived as a way to democratise higher education, to really open education and training. But first studies highlight that most of the enrolled students in MOOC belong to social privileged classes (Christensen & al, 2013; Ho & al, 2014; 2015). According to that results, could we still argue that MOOC contribute to a democratisation of higher education? This study examines French situation. Using data collection (n=5709) from an ad hoc questionnaire disseminated to 12 MOOC offered by the french government platform France Université Numérique (FUN), we found differences between American MOOC student profile and French MOOC student. But they both share privileged socioeconomic status, according to their level of education and nature of employment. These social characteristics influence MOOC access and use. If we could interpret these fundings as a « segregative democratisation » (Merle, 2000), it’s seems most appropriate to talk about massification. Indeed, despite MOOC openess, their use as educational leisure or training resources by a socially privileged audience seem to perpetuate inequalities of both cultural and educational field and reinforce disparities.